2015
DOI: 10.1186/s12890-015-0122-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of nonspecific interstitial pneumonia correlates with perivascular CD4+ T lymphocyte infiltration of the lung

Abstract: BackgroundNonspecific interstitial pneumonia (NSIP) is characterized by interstitial infiltration of T lymphocytes, and subpopulations of these cells may be associated with the progression of fibrosis. However, few studies evaluate the correlation of prognosis with this characteristic. Therefore, we performed morphological and quantitative analyses of T lymphocytes in patients with NSIP and evaluated the relationship between T lymphocytes and prognosis.MethodsImmunohistochemistry was used to detect the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(37 reference statements)
2
1
0
Order By: Relevance
“…We demonstrated that an inflammatory component was absent in the non-fibrotic areas, suggesting that inflammation does not precede fibrogenesis and may even be reactive to fibrogenesis. Furthermore, in contrast to cNSIP lungs (42,43), we found no association between lymphocytes and survival in FPF lungs, further supporting that the degree of lymphocyte aberrations in FPF lungs may not contribute significantly to disease pathogenesis (26,44). In contrast, it has been reported that elevated numbers of lymphocytes are associated with less progressive fibrosis in patients with sIPF (45,46) and cause resistance to bleomycin in mouse models of pulmonary fibrosis (47).…”
Section: Discussionsupporting
confidence: 54%
“…We demonstrated that an inflammatory component was absent in the non-fibrotic areas, suggesting that inflammation does not precede fibrogenesis and may even be reactive to fibrogenesis. Furthermore, in contrast to cNSIP lungs (42,43), we found no association between lymphocytes and survival in FPF lungs, further supporting that the degree of lymphocyte aberrations in FPF lungs may not contribute significantly to disease pathogenesis (26,44). In contrast, it has been reported that elevated numbers of lymphocytes are associated with less progressive fibrosis in patients with sIPF (45,46) and cause resistance to bleomycin in mouse models of pulmonary fibrosis (47).…”
Section: Discussionsupporting
confidence: 54%
“…We demonstrated that an inflammatory component was absent from the non-fibrotic areas, suggesting that inflammation does not precede fibrogenesis and may even be reactive to fibrogenesis. Furthermore, in contrast to cNSIP lungs (85,86), we found no association between lymphocytes and survival in FPF lungs, further supporting the view that the degree of lymphocyte aberrations in FPF lungs may not contribute significantly to disease pathogenesis (64,87). In fact, it has been reported that elevated numbers of lymphocytes are associated with less progressive fibrosis in patients with sIPF (88,89) and cause resistance to bleomycin in mouse models of pulmonary fibrosis (90).…”
Section: Inflammatory and Fibrotic Tissue Remodelling In Pulmonary Fi...supporting
confidence: 77%
“…Telomeres are short TTAGGG DNA tandem repeats at the ends of chromosomes, acting as a buffer in cell-cycle-dependent shortening of DNA, thereby preventing loss of genomic information (83)(84)(85). During healthy aging, leukocyte telomere length declines by approximately 20-30 base pairs per year (86), while in blood leukocytes of patients with pulmonary fibrosis and a TERT mutation telomeres shorten progressively compared to controls and other ILDs (87).…”
Section: Figure 1 Telomerase Machinery and Involved Gene Productsmentioning
confidence: 99%